2007
DOI: 10.1016/j.devcel.2007.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric CLASP-Dependent Nucleation of Noncentrosomal Microtubules at the trans-Golgi Network

Abstract: Proper organization of microtubule arrays is essential for intracellular trafficking and cell motility. It is generally assumed that most if not all microtubules in vertebrate somatic cells are formed by the centrosome. Here we demonstrate that a large number of microtubules in untreated human cells originate from the Golgi apparatus in a centrosome-independent manner. Both centrosomal and Golgi-emanating microtubules need gamma-tubulin for nucleation. Additionally, formation of microtubules at the Golgi requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
599
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 447 publications
(629 citation statements)
references
References 40 publications
(48 reference statements)
28
599
0
2
Order By: Relevance
“…7). These results indicate that MTCL1 plays essential roles in the stable growing of MTs from the Golgi membrane, as has been demonstrated for CLASPs and AKAP450/ CG-NAP 8,9 .…”
supporting
confidence: 76%
See 2 more Smart Citations
“…7). These results indicate that MTCL1 plays essential roles in the stable growing of MTs from the Golgi membrane, as has been demonstrated for CLASPs and AKAP450/ CG-NAP 8,9 .…”
supporting
confidence: 76%
“…5b). Previous studies have shown that the CLASPs complex preferentially localizes to the trans-Golgi region 8 , whereas the AKAP450/CG-NAP complex localizes to the cis-Golgi region 9 . Immunofluorescent staining of MTCL1 showed many overlaps not only with the signals of the CLASPs complex, but also with those of the AKAP450/CG-NAP complex (which was identified by an anti-GM130 antibody, because of lack of an appropriate antibody for double staining; Fig.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Importantly, to provide a sufficient number of microtubules for cargo exit, the TGN membranes themselves are capable of nucleating microtubules. This process is carried out by the microtubule-associated protein CLASP, which interacts with the trans-Golgi protein GCC185 (Efimov et al, 2007). To regulate microtubule nucleation, CLASP might cooperate with CLIP-170, which itself stabilizes microtubules via binding to IQGAP, and which is under the control of Cdc42 (Fukata et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Those various observations raise the possibility of a causal relationship between Golgi dysmorphology and the mitotic spindle defects that accompany hSac1 depletion. In that regard, recent work demonstrates TGN membranes have an intrinsic capability to nucleate MTs (Efimov et al, 2007). Because the TGN seems enriched in PtdIns-4-P, this raises the possibility that excess PtdIns-4-P directly results in precocious nucleation of spindle poles.…”
Section: Sac1 and Progression Through The Cell Cyclementioning
confidence: 99%